Xenon Trapping in Metal‐Supported Silica Nanocages. Issue 39 (31st August 2021) - Xu, Yixin; Dorneles de Mello, Matheus; Zhou, Chen; Sharma, Shruti; Karagoz, Burcu; Head, Ashley R.; Darbari, Zubin; Waluyo, Iradwikanari; Hunt, Adrian; Stacchiola, Dario J.; Manzi, Sergio; Boscoboinik, Alejandro M.; et al.
Abstract: Xenon (Xe) is a valuable and scarce noble gas used in various applications, including lighting, electronics, and anesthetics, among many others. It is also a volatile byproduct of the nuclear fission of uranium. A novel material architecture consisting of silicate nanocages in contact with a metal surface and an approach for trapping single Xe atoms in these cages is presented. The trapping is done at low Xe pressures and temperatures between 400 and 600 K, and the process is monitored in situ using synchrotron‐based ambient pressure X‐ray photoelectron spectroscopy. Release of the Xe from the cages occurs only when heating to temperatures above 750 K. A model that explains the experimental trapping kinetics is proposed and tested using Monte Carlo methods. Density functional theory calculations show activation energies for Xe exiting the cages consistent with experiments. This work can have significant implications in various fields, including Xe production, nuclear power, nuclear waste remediation, and nonproliferation of nuclear weapons. The results are also expected to apply to argon, krypton, and radon, opening an even more comprehensive range of applications. Abstract : In this work, a material is produced using silica nanocages supported on a thin ruthenium film to explore its behavior toward Xe trapping. Synchrotron‐based ambient pressure X‐ray photoelectron spectroscopy (AP‐XPS) is used to follow the Xe trapping, exploring mechanistic aspects of this process by combining experimental, theoretical, and simulation tools.